Assisted reproductive technology and association with childhood cancer subtypes. (5th August 2022) - Gulrajani, Natalie B.; Montes, Samuel; McGough, Daniel; Wimberly, Courtney E.; Khattab, Ameera; Semmes, Eleanor C.; Towry, Lisa; Cohen, Jennifer L.; Hurst, Jillian H.; Landi, Daniel; Hill, Sherika N.; Walsh, Kyle M.
Abstract: Objectives: To investigate the association between assisted reproductive technology (ART) use and childhood cancer subtype. Study Design: We deployed a cross‐sectional survey of 1701 parents of children with cancer about their ART use, demographics, and gestational and perinatal factors. Multivariable logistic regression modeled the association between ART use, birthweight and multiple gestation status with childhood cancer, by subtype. Results: ART use was highest among children with osteosarcoma relative to children with other cancer types, and this association was statistically significant in multivariable models (OR = 4.4; 95% CI = 1.7–11.3; p  = 0.0020). ART use was also elevated among children with hepatoblastoma, but this relationship appeared to be due to the strong associations between ART use and lower birthweight in our sample. No specific ART modality appeared to drive these associations. In univariate models, multiple gestation was associated with a 2.7‐fold increased odds of hepatoblastoma (OR = 2.71; 95% CI = 1.14–6.42; p  = 0.02) and a 1.6‐fold increased odds of neuroblastoma (OR = 1.62; 95% CI = 1.03–2.54; p  = 0.03), but these associations were not retained in multivariable models. Conclusions: Associations between ART use and hepatoblastoma risk may be attributable to birthweight, a known hepatoblastoma risk factor. ART use may also be associated with osteosarcoma, independent of birthweight, an association not previously observed in studies limited to cancers diagnosed before adolescence. Evaluating long‐term health outcomes in children conceived by ART, throughout adolescence and potentially into adulthood, appears warranted. Abstract : Epidemiologic data suggest an increase in U.S. childhood cancer incidence overall, though rates vary across cancer subtypes and few modifiable risk factors for childhood cancer have been identified. A cross‐sectional survey of 1701 parents of children with cancer revealed associations between use of assisted reproductive technology and risk of childhood hepatoblastoma and osteosarcoma. the latter of which has not been previously observed in studies limited to cancers before adolescence. Evaluating long‐term health outcomes in children conceived by ART, throughout adolescence and potentially into adulthood, appears warranted.